2020
DOI: 10.3389/fsufs.2020.562663
|View full text |Cite
|
Sign up to set email alerts
|

Maize-Pigeonpea Intercropping Outperforms Monocultures Under Drought

Abstract: There is an urgent need to develop resilient agroecosystems capable of helping smallholder farmers adapt to climate change, particularly drought. In East Africa, diversification of maize-based cropping systems by intercropping with grain and tree legumes may foster productivity and resilience to adverse weather conditions. We tested whether intercropping enhances drought resistance and crop and whole-system yields by imposing drought in monocultures and additive intercrops along a crop diversity gradient—sole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Increasing crop diversity at multiple scales, from intercropping to whole farms to regional scales, can also reduce drought risk in ways other than changes to soil (Lin, 2011;Renwick et al, 2020). Increasing the diversity of crops grown at the farm-scale to include ones that differ in their water use, drought tolerance, or phenology helps reduce risks to farm-level yield and income through a "portfolio effect" (Helmers et al, 2001, Isbell et al, 2017.…”
Section: Diversifying Pathway Opportunities and Barriers To Increasinmentioning
confidence: 99%
“…Increasing crop diversity at multiple scales, from intercropping to whole farms to regional scales, can also reduce drought risk in ways other than changes to soil (Lin, 2011;Renwick et al, 2020). Increasing the diversity of crops grown at the farm-scale to include ones that differ in their water use, drought tolerance, or phenology helps reduce risks to farm-level yield and income through a "portfolio effect" (Helmers et al, 2001, Isbell et al, 2017.…”
Section: Diversifying Pathway Opportunities and Barriers To Increasinmentioning
confidence: 99%
“…Productivity gains were often highly site specific. For example, a study by Renwick et al (2020) found that whole-system crop yield was consistent with that of the control for maize-pigeonpea intercropping and negatively impacted by maize-pigeonpea-gliricidia intercropping, except under drought conditions, where maize-pigeonpea-gliricidia intercropping increased maize yield. Compared to monoculture controls, Renwick et al (2020) consistently found that intercropping with maize and pigeonpea produced the same yield on less land, or a land equivalent ratio (LER) greater than 1, suggesting positive mitigation outcomes as a result of increased agronomic efficiency.…”
Section: Productivity Resilience and Mitigationmentioning
confidence: 78%
“…For example, a study by Renwick et al (2020) found that whole-system crop yield was consistent with that of the control for maize-pigeonpea intercropping and negatively impacted by maize-pigeonpea-gliricidia intercropping, except under drought conditions, where maize-pigeonpea-gliricidia intercropping increased maize yield. Compared to monoculture controls, Renwick et al (2020) consistently found that intercropping with maize and pigeonpea produced the same yield on less land, or a land equivalent ratio (LER) greater than 1, suggesting positive mitigation outcomes as a result of increased agronomic efficiency. In the same study, findings showed that, while intercropping with a leguminous crop (pigeonpea) consistently produced an LER greater than 1, introducing an agroforestry species (gliricidia) only had positive mitigation outcomes under certain conditions (unfertilized ambient conditions and fertilized drought conditions).…”
Section: Productivity Resilience and Mitigationmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, fuelwood production should not impair food production. Studies from the same research site showed that the integration of Gliricidia and pigeon pea in cropping plans does not lead to crop yield loss but bears the potential to yield more using less area (sustainable intensification) [51,52]. The introduction of agroforestry systems needs to consider the whole crop/tree value chain, including the availability of seeds, the availability of seedlings, the growth rates, the local interests, as well as the marketability of the product [8].…”
Section: Adoption Of On-farm Fuel Production Systemsmentioning
confidence: 99%